Degradable cellulose‐based polymer brushes with controlled grafting densities. Issue 24 (29th August 2019) - Olszewski, Mateusz; Li, Lingchun; Xie, Guojun; Keith, Andrew; Sheiko, Sergei S.; Matyjaszewski, Krzysztof
ABSTRACT: Cellulose‐based polymer brushes with variable grafting densities and low dispersity were synthesized by grafting poly( n ‐butyl acrylate) (PBA) side chains from cellulose‐derived backbones via ATRP. Esterification of commercially available cellulose acetate with 2‐bromoisobutyryl bromide (2‐BiBB) in NMP provided cellulose‐based macroinitiators averaging one initiation site per double glucose unit. ATRP macroinitiators averaging up to 6 initiation sites per repeating double glucose unit were prepared by acylation of microcrystalline cellulose (MCC) in LiCl/DMAc solvent system with 2‐BiBB. A series of linear macroinitiators with narrow MWD were obtained by fractional precipitation process. The content of initiating sites was determined by elemental analysis. (Meth)acrylate side chains were then grafted from the cellulose‐based macroinitiators. The prepared cellulose‐based polymer brushes showed tunable degradation rates dependent on grafting density of the brush, following two different degradation pathways, either cleavage of the main chain or detachment of the side chains. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 2426–2435 Abstract : Cellulose‐based molecular bottlebrushes were prepared. A series of macroinitiators with varying grafting densities were prepared by chemical modification and fractional precipitation. Molecular bottlebrushes were prepared using "grafting from" atom transfer radical polymerization of butyl acrylate. These cellulose‐based bottlebrushes are degradable. Two different degradation pathways are proposed that result in degradation rates dependent on grafting density. Atomic force imaging was used to show that cellulose‐based bottlebrushes take up different conformations and more rigid characteristics with increasing grafting density.